The effect of brand communication and brand image on brand loyalty through brand trust on good day drink products in Surabaya - Ellitan, Lena; Pradana, Septiano Bintang (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
In this era, companies are competing to be the best in the business they are in, including the beverage business. Especially now that there are more and more consumer needs and desires to fulfill their satisfaction, one of which is the coffee beverage business. In the coffee beverage business, which is currently growing very rapidly in Indonesia, it has demanded that companies be able to be the best and want to always maintain their existence, one of which is by improving the quality of taste and making it easier for consumers to consume coffee. and is seen as the most practical and preferred drowsiness reliever by all circles. This study aims to analyze the effect of brand communication and brand image on brand loyalty through brand trust in Good Day beverage products in Surabaya. The object of this research is consumers who have ever drank Good Day beverage products in Surabaya. The research sample used in this study was 150 samples with purposive sampling technique. The data used is primary data obtained by distributing questionnaires to consumers who have used Good Day beverage products in Surabaya via google form. The data analysis technique used is SEM with the help of PLS. The results show that brand communication is significant positive for brand image, significant positive brand communication is on brand trust, brand image is significant positive for brand trust, brand trust is significant positive for brand loyalty.